Effect of Copper Oxide and Manganese Oxide on Properties and Low Temperature Degradation of Sintered Y-TZP Ceramic - Khan, M.M.; Ramesh, S.; Bang, L.T.; Wong, Y.H.; Ubenthiran, S.; Tan, C.Y.; Purbolaksono, J.; Misran, H. (ASM International, 2014)
The effect of copper oxide (CuO) and manganese oxide (MnO2) co-dopant on the densification behavior of 3 mol% yttria-stabilized zirconia was investigated. Green samples were prepared and sintered in air at temperatures ranging from 1250 to 1500 °C with a short holding time of 12 min. Sintered bodies were characterized to determine the phase stability, bulk density, hardness, fracture toughness, Young’s modulus and grain size. In addition, the aging-induced tetragonal to monoclinic phase transformation of the sintered zirconia was evaluated. It was revealed that the addition of CuO-MnO2 co-dopant was beneficial in enhancing the densification and mechanical properties of the ceramic particularly at low temperatures. A high fracture toughness of 5.5 MPam1/2 coupled with high hardness of 14.5 GPa was obtained for co-doped samples sintered at 1350 °C. However, the undoped ceramic exhibited better properties when sintered above 1350 °C. The study also found that the dopants did not prevent grain coarsening and hence did not suppress the aging-induced phase transformation particularly for samples sintered above 1350 °C.